Myosin sequestration regulates sarcomere function, cardiomyocyte energetics, and metabolism, informing the pathogenesis of hypertrophic cardiomyopathy - Toepfer, CN; Garfinkel, AC; Venturini, G; Wakimoto, H; Repetti, G; Alamo, L; Sharma, A; Agarwal, R; Ewoldt, JF; Cloonan, P; Letendre, J; Lun, M; et al. (American Heart Association, 2020)
Background: Hypertrophic cardiomyopathy (HCM) is caused by pathogenic variants in sarcomere protein genes that evoke hypercontractility, poor relaxation, and increased energy consumption by the heart and increased patient risks for arrhythmias and heart failure. Recent studies show that pathogenic missense variants in myosin, the molecular motor of the sarcomere, are clustered in residues that participate in dynamic conformational states of sarcomere proteins. We hypothesized that these conformations are essential to adapt contractile output for energy conservation and that pathophysiology of HCM results from destabilization of these conformations.